Effects of calcium antagonists and agonists on isolated human v. saphena magna used for coronary artery bypass grafting and guinea pig’s papillary muscle - Garaliene, Vida; Barsys, Vygantas; Jakuška, Povilas; Krauze, Aivars; Duburs, Gunar (Arzneimittelforschung, 2011)
The goal of this study was to investigate the movement of contraction-relaxation effects on isolated human blood vessel samples by the actions of amlodipine (CAS 88150-42-9), cerebrocrast (CAS 118790-71-9), diltiazem (CAS 42399-41-7), and a benzimidazole derivative. Additionally, their effects on isometric contraction force and the duration of the action potential (AP) were measured.The experiments were carried out on isolated human v. saphena magna samples and papillary muscles of adult guinea pigs. Isometric contraction and the AP were recorded using a force transducer and standard microelectrode technique.Phenylephrine (10−4 M) caused contractions of vein rings to 928 ± 76.5 mg. All the tested agents at a concentration of 10−7–10−4 M significantly relaxed the smooth muscle in a dose-dependent manner. The weakest response was shown by amlodipine. Pre-treatment with 50 >M of amlodipine, diltiazem and benzimidazole for 30 min significantly increased the magnitude of the contraction induced by phenylephrine in concentration-dependent (10−6–10−4) fashion but only in the benzimidazole group versus other tested agents and the control. The benzimidazole derivative caused augmentation of isometric contraction of the papillary muscles and negligible lengthening of AP duration; the other agents tested showed opposite effects.These results show that agents possessing positive or negative inotropic action significantly relaxed the isolated vein samples precontracted with phenylephrine. These responses point to a different mechanism of action underlying both calcium antagonist and agonist effects even though their action ultimately resulted in vasodilatation.
Keywords: 1-Acetyl-5,6-dimethoxy-2-methylthiobenzimidazole; Amlodipine; Cerebrocrast; Diltiazem; Guinea pig papillary muscles; Human v. saphena magna